The Curriculum Of Arabic Language Skills For Non-Native Speakers In Sri Lankan Government Universities - Mohammed Thamby Habeebullah (Bumi Lingua Edu Center, 2025)
This study aims to evaluate the Arabic language skills curriculum designed for students of Arabic as a foreign language at Sri Lankan Government Universities. Even though there are four Government Universities in Sri Lanka that teach Arabic, many studies have shown gaps and a lack of effectiveness in Arabic learning among students in attaining the desired high-level proficiency in listening, speaking, reading, and writing. Thus, the researcher aims to determine why failures and gaps in student achievement occur due to deficiencies in the existing Arabic language skills curriculum at these Universities. The research approach is descriptive, analytical, and evaluative, with secondary sources used to present details of the current Arabic-language skills curriculum in Government Universities of Sri Lanka. The researcher finds that the present curriculum has several weaknesses, loopholes, and limitations, and thus recommends redesigning it to enhance learners' mastery of Arabic as a foreign language.